Cationic Polymerization Induced by Tris-(p-bromophenyl) Amine Cation-Radical Salts - Abu-Abdoun, Ideisan I. (Journal of Research Updates in Polymer Science, 2019)
Substituted triphenylamine cation radical salts having anions of the type SbF6-, PF6-, BF4- and SbCl6-, were prepared and used to initiate cationic polymerization of cyclohexene oxide (CHO), tetrahydrofuran (THF), and N-vinyl carbazole (NVC), thermally in dichloromethane at room temperature. Experimental results are presented to show the effects of salt counter ion, concentration, and polymerization conditions on the yield and the molecular weight of the obtained polymer. THF polymerization was enhanced by photolysis of the reaction mixture for short time. A general mechanism for the polymerization by cation-radical salts of substituted triphenylamine is proposed.